The Role of PPKn Teachers in Preventing Bullying at SMA Negeri 8 Surakarta - Faustine, Vanessa Viona; Sunarto, Sunarto; Isdaryanto, Noorochmat (Universitas Negeri Semarang, 2023)
Bullying is an action taken by a person or group of people verbally, physically or psychologically so that the victim feels helpless. This research was conducted at SMA Negeri 8 Surakarta using qualitative methods. Collection of research data obtained through secondary data sources. Data validity techniques used method triangulation and source triangulation, and data analysis techniques were carried out by collecting data, presenting data, reducing data, and drawing conclusions from data. The results showed that the role of civic teachers in preventing bullying was divided into two, namely direct action, such as giving encouragement to victims of bullying. While indirect actions can be divided into two, namely, first, intracurricular actions, such as through brainstorming techniques, through role playing techniques, supervision techniques. Second, co-curricular actions such as holding delta cast interactive dialogue events, bullying counseling activities, and holding discussions with other teachers. The school's role in preventing bullying is the declaration of a child-friendly school and routinely holding FAS activities. The obstacles experienced by PPKn teachers are divided into two, namely the first intra-curricular constraints and co- curricular constraints.